Key-risk factors for fracture-related infection after ankle surgery: a retrospective study - Serrasqueiro, Sebastiao N.; Simões, Orlando; Moreno, João; Pinheiro, Vitor; Fonseca, Fernando (International Journal of Research in Orthopaedics, 2024)
Background: Fracture-related infection (FRI) is a serious complication following ankle fracture surgery, with significant implications for patient outcomes. This study aimed to identify the key risk factors associated with FRI in a cohort of patients undergoing surgical fixation of ankle fractures. Methods: A retrospective analysis was conducted on 261 patients who underwent open reduction and internal fixation (ORIF) for ankle fractures between 2019 and 2021. Patient demographics, comorbidities, and surgical details were extracted from medical records. The primary outcome was the development of FRI within one year postoperatively. Logistic regression analysis was used to identify independent predictors of infection. Results: The mean age of the patients was 61.8 years (SD=16.5), with 69.3% being female. The overall infection rate was 8%. Significant predictors of FRI included smoking (OR=13.643, p=0.002), peripheral vascular disease (OR=17.684, p<0.001), and diabetes mellitus (OR=11.309, p=0.002). Gender, congestive heart failure, obesity, and age were not statistically significant predictors of infection. Conclusion: This study identifies smoking, peripheral vascular disease, and diabetes mellitus as significant risk factors for FRI following ankle fracture surgery. These findings underscore the importance of targeted interventions to manage these comorbidities in high-risk patients to reduce the incidence of postoperative infections. Further research is needed to explore the role of other potential factors and to develop effective prevention strategies.